Age-Related Changes in the Natural Killer Cell Response to Seasonal Influenza Vaccination Are Not Influenced by a Synbiotic: a Randomised Controlled Trial - Przemska-Kosicka, Agnieszka; Childs, Caroline E.; Maidens, Catherine; Dong, Honglin; Todd, Susan; Gosney, Margot A.; Tuohy, Kieran Michael; Yaqoob, Parveen (Frontiers in Immunology, 2018)
Natural killer (NK) cells are an important component of the immune response to influenza infection, but are subject to alteration during ageing, which may play a role in impaired response to infection and vaccination in older people. Enhancement of NK cell activity could, therefore, present a means to improve the immune response to vaccination in older subjects, and pre- and probiotics offer an opportunity to modulate anti-viral defences via alteration of the gut microbiota. This study investigated the effect of a novel probiotic, Bifidobacterium longum bv. infantis CCUG 52486, combined with a prebiotic, gluco-oligosaccharide (B. longum + Gl-OS), on the NK cell response to seasonal influenza vaccination in young and older subjects in a double-blind, randomized controlled trial. There were significant effects of ageing on NK cell phenotype, the most notable of which were an increase in CD56dim cells, mainly reflected in the CD16+ subset, a decrease in CD56bright cells, mainly reflected in the CD16- subset, and greater expression of the immunosenescence marker, CD57, on NK cell subsets. However, these changes only partially translated to differences in NK cell activity, observed as trends towards reduced NK cell activity in older subjects when analysed on a per cell basis. Influenza vaccination increased the proportion of CD56bright cells and decreased the proportion of CD56dim cells, in young, but not older subjects. Although NK cell activity in response to vaccination was not significantly different between the young and older subjects, low post-vaccination NK cell activity was associated with poor seroconversion in only the older subjects. There was no influence of the synbiotic on NK cell phenotype or activity, either before or after influenza vaccination. In conclusion, ageing is associated with marked alteration of the phenotype of the NK cell population and there was evidence of an impaired NK cell response to influenza vaccination in older subjects. The effects of ageing on NK cell phenotype and activity could not be offset by B. longum + Gl-OS. Clinical trial identifier: clinicaltrials.gov NCT01066377.